Piezoelectric Transducers and Applications - Vives, Antonio Arnau; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
New understandings underlying the principles of Piezoelectric Transducers, new technological advances in its applications, and new areas of utility for these transducers made a second edition of this book inevitable. The second edition of Piezoelectric Transducers and Applications includes these new developments together with a deep revision and enlargement of the topics already included in the first edition. It provides a guide for graduate students and researchers to the current state of the art of this complex and multidisciplinary area. The book fills an urgent need for a unified source of information on piezoelectric devices and their astounding variety of existing and emerging applications. Some of the chapters focus more on the basic concepts of the different disciplines involved and are presented in a didactic manner. Others go deeper into the complex aspects of specific fields of research, thus reaching the technical level of a scientific paper. Among other topics resonant sensors, especially bulk acoustic wave thickness shear mode resonators, chemical and bio-sensors, as well as broadband ultrasonic systems are treated in-depth.
Fundamentals of Piezoelectricity -- Overview of Acoustic-Wave Microsensors -- Models for Resonant Sensors -- Models for Piezoelectric Transducers Used in Broadband Ultrasonic Applications -- Interface Electronic Systems for AT-Cut QCM Sensors: A comprehensive review -- Interface Electronic Systems for Broadband Piezoelectric Ultrasonic Applications: Analysis of Responses by means of Linear Approaches -- Viscoelastic Properties of Macromolecules -- Fundamentals of Electrochemistry -- Chemical Sensors -- Biosensors: Natural Systems and Machines -- Modified Piezoelectric Surfaces -- Fundamentals of Piezoelectric Immunosensors -- Combination of Quartz Crystal Microbalance with other Techniques -- QCM Data Analysis and Interpretation -- Sonoelectrochemistry -- Ultrasonic Systems for Non-Destructive Testing Using Piezoelectric Transducers:.Electrical Responses and Main Schemes -- Ultrasonic Techniques for Medical Imaging and Tissue Characterization -- Ultrasonic Hyperthermia.
Keywords: Engineering; Control engineering; Robotics; Mechatronics; Electronics; Microelectronics; Optical materials; Electronic materials; Nanotechnology; Engineering; Electronics and Microelectronics, Instrumentation; Optical and Electronic Materials; Nanotechnology; Control, Robotics, Mechatronics; Electronic books